2020
DOI: 10.1101/2020.07.04.187161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calmodulin acts as a state-dependent switch to control a cardiac potassium channel opening

Abstract: AbstractCalmodulin (CaM) and PIP2 are potent regulators of the voltage-gated potassium channel KCNQ1 (KV7.1), which conducts the IKs current important for repolarization of cardiac action potentials. Although cryo-EM structures revealed intricate interactions between the KCNQ1 voltage-sensing domain (VSD), CaM, and PIP2, the functional consequences of these interactions remain unknown. Here, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…The CTD-bent state allows interactions between CaM and the VSD, which are disrupted in the CTD-straight channel. Recent studies showed that both states are present in the channel activation pathway [21]. to not significantly increase signaling efficiency alone.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CTD-bent state allows interactions between CaM and the VSD, which are disrupted in the CTD-straight channel. Recent studies showed that both states are present in the channel activation pathway [21]. to not significantly increase signaling efficiency alone.…”
Section: Resultsmentioning
confidence: 99%
“…1 shows a flowchart of how the network is built using MD simulation data. We use a continuous contact map and positional mutual information to model spatial proximity and correlation of residue movements, respectively (see details below) [21].…”
Section: A Constructing a Residue Interaction Networkmentioning
confidence: 99%
See 3 more Smart Citations